The political economy of the Eurozone - Cardinale, Ivano; Coffman, D'Maris 1973-; Scazzieri, Roberto 1950- (Cambridge University Press, 2017)
This book proposes a new way of thinking about the Eurozone, exploring the overlap between its economic and political interdependencies